To solve this system of equations by substitution, we need to first solve for y in terms of x in the second equation, and then substitute that expression into the first equation.
Given:
y = 3x - 4
We will substitute y in the first equation:
-4x + 4(3x - 4) = -40
-4x + 12x - 16 = -40
8x - 16 = -40
8x = -24
x = -3
Now, we will substitute x back into the equation y = 3x - 4 to solve for y:
y = 3(-3) - 4
y = -9 - 4
y = -13
Therefore, the solution to the system of equations is x = -3 and y = -13.
Solve the system of equations by substitution.%0D%0A%0D%0A−4x+4y=−40%0D%0A−%0D%0A4%0D%0A%0D%0A+%0D%0A4%0D%0A%0D%0A=%0D%0A−%0D%0A40%0D%0A%0D%0Ay=3x−4
1 answer